ANALISIS PENGARUH PRINSIP KEHATI-HATIAN AKUNTANSI DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2016) - Florentia Eveline R. K.; Sri Handayani (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to analyze the effect of accounting conservatism and institutional ownership toward earnings management using audit quality and executive compensations as the control variables. This study replicates the research conducted by Lin et al. (2014). In contrast to the research by Lin et al. (2014), this study used Real Profit Management as a proxy for earnings management, and added Audit Quality and Executives Compensations as control variables. The population used in this study are 287 manufacture companies listed in Indonesia Stock Exchange during 2015-2016. The sampling method used is purposive sampling without replacement with documentation techniques. This study examined the effect of accounting conservatism and institutional ownership toward earnings management by descriptive statistical tests, classical assumptions tests, and regression analysis.The results of this study indicated that companies with high accounting conservatism are able to limits earnings management practices. This study also shows that companies with high proportion of institutional ownerships are able to reduces the level of earnings management due to the great monitoring function by institutional investors.